The liminal and inconclusive rites of passage in Tsotsi and District 9 - Zhang, Jane Yu Fang (2011)
The focus of this paper highlights the significance of liminality. Filmed in post apartheid South Africa, in 2005 and 2009 respectively, Tsotsi and District 9 address current and concrete issues pertaining to the country’s historical and political conditions. A close study of the mise-en-scene analyzed in relation to the lead character’s predicament highlights the layers of power relation at work. Using a network of relations amongst characters of difference race, class and nationality, these films explore the essence of power disparity. This paper will discuss how such power disparity contributes to the character’s alienation and propel their entrapment in liminal spaces. Through this discussion I will highlight how Gramsci’s research on hegemonic forces grants us an insight to the regulant uncertainty which Tsotsi and Wikus struggle to overcome. More prominently, this paper will illustrate how Foucault’s ideas on power relations offer an explanation for the vague and ambiguous endings as depicted in both films. With Tsotsi’s inconclusive surrender and Wikus’s unknown state of condition, their indeterminable future intensifies this air of uncertainty. Following a close analysis of the character’s predicament in time and space, coupled with concepts of the abject, we witness how their individual experience serves to emphasize the ambivalent future of South Africa at large.